2013
DOI: 10.1186/1475-2875-12-148
|View full text |Cite
|
Sign up to set email alerts
|

Severe Plasmodium falciparum and Plasmodium vivax malaria among adults at Kassala Hospital, eastern Sudan

Abstract: BackgroundThere have been few published reports on severe Plasmodium falciparum and Plasmodium vivax malaria among adults in Africa.MethodsClinical pattern/manifestations of severe P. falciparum and P. vivax (according to World Health Organization 2000 criteria) were described in adult patients admitted to Kassala Hospital, eastern Sudan.ResultsA total of 139 adult patients (80 males, 57.6%) with a mean (SD) age of 37.2 (1.5) years presented with severe P. falciparum (113, 81.3%) or P. vivax (26, 18.7%) malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
2
40
4
1
Order By: Relevance
“…The area is characterized by unstable malaria transmission [11]. The detail of the method and clinical part of the study was published recently [12]. In summary, after patients or guardians (in cases of comatose patients and children) signed an informed consent form, clinical data (temperature, weight, and fever history) were collected using questionnaires.…”
Section: Patientsmentioning
confidence: 99%
“…The area is characterized by unstable malaria transmission [11]. The detail of the method and clinical part of the study was published recently [12]. In summary, after patients or guardians (in cases of comatose patients and children) signed an informed consent form, clinical data (temperature, weight, and fever history) were collected using questionnaires.…”
Section: Patientsmentioning
confidence: 99%
“…Vivax malaria does not have a benign course and this has been reported in several recent studies. (3)(4)(5)(6)14) .17% of our patients had splenomegaly while 13% had hepatomegaly. Splenomegaly was more common in mixed and vivax infections than in falciparum infections while hepatomegaly was more common in mixed and falciparum infections than in vivax infections.…”
Section: Discussionmentioning
confidence: 99%
“…(3)(4)(5)(6) A considerable number of patients are even presenting with mixed infection.The present study was conducted to do a comparative analysis of clinical presentation, diagnosis, biochemical and hematological profile of patients presenting with vivax falciparum and mixed infections in a peripheral hospital of Mumbai.…”
Section: Introductionmentioning
confidence: 99%
“…CFR were also lower among Plasmodium vivax infected individuals [43]. However, an Indian study showed that several complications including acute kidney injury, jaundice, severe anemia, metabolic acidosis, shock, hyperpyrexia, hypoglycemia, or generalized tonicclonic seizures were more prevalent in patients with Plasmodium vivax malaria than Plasmodium falciparum malaria [44].…”
Section: Dysglycaemia and Other Plasmodium Speciesmentioning
confidence: 99%